Leisure, sport and tourism, politics policy and planning - Veal, Anthony James (Wallingford, Oxfordshire, UK CABI, 2017)
A comprehensive, multidisciplinary approach to public policymaking and planning in the leisure, sport and tourism sectors, this book: - examines the theoretical issues underpinning public sector policymaking such as political ideologies, leisure wants, needs, demand and benefits, and human rights in leisure, sport, tourism and culture; - discusses the debates surrounding the role of the state versus market, and models of organizational decision-making; and - uses applied sections addressing strategic planning and performance evaluation to provide a link between theory and practical analytical techniques. As well as extensive updating of sources, this new edition examines such topics as libertarianism, theocracy, anti-establishment politics, and the concept of generations. A new chapter presents discussions of a number of 'issues and challenges' facing the leisure, sport and tourism sector. Introducing the subject for undergraduate and postgraduate students of leisure, sport and tourism, this book is also a useful addition to the shelf of any policy maker or practitioner within the industries.
I. SOCIETY, POLITICS, POLICY & PLANNING : 1 Introduction. 2 Political ideologies. 3 Wants, needs, obligations, etc. 4 Human rights and citizenship rights. 5 The market versus the state -- II. PLANNING FRAMEWORKS : 6 Public policy-making. 7 Types of plan. 8 Evaluating approaches to planning. 9 U-Plan: participation-based approach to planning -- III : PLANNING TOOLS 10 Planning tool 1: Consultative. 11 Planning tool 2: Facility/service audit : Process & Capacity. 12 Planning tool 3 : Facility/service audit: Facility use/assessment. 13 Planning tool 4: Forecasting demand. -- IV: EVALUATION : 14 Economic evaluation. 15 Performance evaluation. -- V: SECTORS, GROUPS & ISSUES : 16 Policy and planning in particular sectors. 17 Policy and planning for particular groups. 18 : Issues/challenges.
Includes bibliographical references and index.
Keywords: Leisure -- Government policy -- Great Britain; Tourism -- Government policy -- Great Britain; Recreation -- Great Britain -- Planning